2005
DOI: 10.1300/j172v05n04_03
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Divide Between Theory and Practice

Abstract: Experiential learning approaches such as role-play have been found to be valuable methods of bridging the divide between academic knowledge and practical skills, a problem often cited in tourism and hospitality management education. Such approaches have been found to contribute towards deeper learning by enhancing students' interest, motivation, participation, knowledge and skill development. This paper reports on the implementation of an experiential learning approach designed to encourage and facilitate deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(34 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…We found that students experience learning satisfaction in terms of teacher training, such as teaching methods, interpersonal relationships, and workplace exploration. The result for workplace exploration is consistent with previous research [15,21]; that is, industry experts possess ample professional knowledge of the workplace. Students were mainly concerned about three items under the workplace exploration construct, namely "Top learning methods in various fields by the collaborative teaching of industry experts," "I was stimulated by different thinking methods by the collaborative teaching of industry experts," and "I gained improved knowledge on industry needs in terms of human resources."…”
Section: Discussionsupporting
confidence: 91%
“…We found that students experience learning satisfaction in terms of teacher training, such as teaching methods, interpersonal relationships, and workplace exploration. The result for workplace exploration is consistent with previous research [15,21]; that is, industry experts possess ample professional knowledge of the workplace. Students were mainly concerned about three items under the workplace exploration construct, namely "Top learning methods in various fields by the collaborative teaching of industry experts," "I was stimulated by different thinking methods by the collaborative teaching of industry experts," and "I gained improved knowledge on industry needs in terms of human resources."…”
Section: Discussionsupporting
confidence: 91%
“…Participating in this particular event provided a sense of experience hardly similar to just reading or learning in class about trends and patterns related to cruise demand. This reinforces the claim made by Ruhanen (2005) that anecdotal evidence and experiences help to bridge the divide between theory and practice for tourism and hospitality management education. LOHMANN "warm," and "helpful" workforce, which Weaver (2005) labels as "performative metaphors," students could also pick up the disparities that exist between the crewmembers' and officers' lifestyle onboard.…”
Section: Data Collectionsupporting
confidence: 83%
“…As a blending strategy, the PFD initiative has been usefully and indeed successfully implemented to bring practitioners' perspectives into the academia to the end of authentic (experiential) learning, and ultimately for bridging the divide between academic knowledge and practical skills (Cooper, 2015;Ruhanen, 2005;Vong, 2017). Notwithstanding, the "insider's" view on the PFD initiative and its associated perspectives have to be acknowledged with caution and care.…”
Section: Resultsmentioning
confidence: 99%
“…Turning to brokering and bridging tactics in knowledge development and education research, an overwhelming body of literature has been built on "theory and practice" (Ruhanen, 2005), "community of practice" (Wenger, 1998), and "experiential learning" (Kayes, 2002). Kolb's (1984) seminal work postulates learning "as a process whereby knowledge is created through the transformation of experience" (p.41).…”
Section: The Title Of a Professor Has A Different Meaning Here It Ismentioning
confidence: 99%
See 1 more Smart Citation